Anthropological Perspectives On Folklore: Underpinnings on Some Nepali Folklore - Upadhyay, Prakash (Tribhuvan University Journal, 2016)
The main objectives of this article is to explore how people use folklore for interaction, and how folklore is useful for managing social/cultural situations for identity making. Pedestal on qualitative secondary data were obtained from various literature, books, journals and articles. The conceptual frame of the study respite on four field approaches of anthropology which comprehend folklore at local, regional, national, and global scales and are supportive in reflecting the understandings in application and seeking ways to adjust with communities to assist them in preserving folklore or in bridging the knowledge-community dissection—understanding and analyzing ethnic behaviors, their identity and institutions, human-culture-nature relation, micro-macro structural relations. With a unique cultural heritage, Nepal is copious with diverse folklore based on legends, religion, popular beliefs etc. They are the traditions of ethnic cultures, subcultures, or groups to express feelings. Nepali folklore establishes relationship of local people with their culture, ethno-cognition, using folklore for interaction and unity, for managing social/cultural/ecological situations in various institutional settings for identity making, explaining the natives as possessing an exclusive system of perceiving and organizing phenomenon. Anthropology’s in-depth fieldwork methodology, long rendezvous in questions of society–culture interactions and broad holistic view yields precious insights into Nepali folklore.